A dressing and its preparation method and application

By using the oriented spinning layer of cross fibers and a high porosity mesh spinning layer in wound dressings, combined with antibacterial and anti-inflammatory substances, the problem of heavy or weak existing dressings is solved, and good absorption and mechanical properties are achieved, reducing the risk of wound infection.

CN119746124APending Publication Date: 2025-04-04SUZHOU RUIJINUO MEDICAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411995585.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, thicker shallow wound dressings affect activity, or are thinner, poorly absorbed and prone to damage, increasing the risk of secondary injury or infection of the wound.

Method used

Using a dressing consisting of an orientation spinning layer and a mesh spinning layer, the orientation spinning layer includes at least two layers of cross-fiber oriented spinning sheets. The mesh spinning layer has a high porosity and antibacterial anti-inflammatory substances, and is prepared by electrospinning method.

Benefits of technology

The dressing maintains sufficient mechanical properties to absorb wound ooze, prevent infection, and provide continuous protection without affecting wound activity, reducing the risk of secondary wound injury.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746124A_ABST
    Figure CN119746124A_ABST
Patent Text Reader

Abstract

The present invention provides a dressing and a preparation method and application thereof, which relates to the technical field of wound dressings, including an oriented spinning layer and a mesh spinning layer respectively arranged on both sides of the oriented spinning layer; the oriented spinning layer includes at least two layers of oriented spinning sheets, and the fiber orientations of adjacent oriented spinning sheets are mutually crossed; the porosity of the oriented spinning layer is 40% to 80%; the porosity of the mesh spinning layer is 50%-85%; the fiber diameters of the mesh spinning layer and the oriented spinning sheet are independently 1nm to 20μm. The dressing is suitable for superficial wounds on the body surface and can absorb wound exudate. At the same time, because the dressing is thin and has excellent mechanical properties, it will not cause inconvenience in the wound and will not damage the dressing due to limb movement. The technical problem that the superficial wound dressing is thick and affects the activity, or is thin and has poor absorption capacity and is easy to break in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wound dressings, and in particular to a dressing and a preparation method and application thereof. Background Art

[0002] Medical dressings cover wounds, which can block dust and pollutants in the air, absorb exudate, pus, blood, etc. secreted from the wound, keep the wound dry, heal quickly, and avoid leaving scars. In cases such as scalds, burns, postoperative wounds, skin acne, etc., dressings are needed to cover and protect the wound and promote wound healing. However, in order to have a strong liquid absorption capacity, the dressings in the prior art are designed as a multi-layer thicker structure; and thin dressings, mostly with non-woven fabrics as the base, need to be replaced regularly during the wound healing process to avoid adhesion, which increases the risk of secondary injury or infection of the wound.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] One of the purposes of the present invention is to provide a dressing to solve the technical problems in the prior art that superficial wound dressings are too thick to affect the activity, or too thin to have poor absorption capacity and be easily damaged.

[0005] A second object of the present invention is to provide a method for preparing the above-mentioned dressing.

[0006] A third object of the present invention is to provide the use of the above-mentioned dressing or the dressing prepared by the above-mentioned preparation method in the preparation of products for promoting wound healing or preventing wound infection.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] In a first aspect, the present invention provides a dressing, comprising an oriented spinning layer and mesh spinning layers respectively arranged on both sides of the oriented spinning layer;

[0009] The oriented spinning layer comprises at least two layers of oriented spinning sheets, and the fiber orientations of adjacent oriented spinning sheets are crossed with each other;

[0010] The porosity of the oriented spinning layer is 40% to 80%;

[0011] The porosity of the mesh spinning layer is 50%-85%;

[0012] The fiber diameters of the mesh spinning layer and the oriented spinning sheet are independently 1 nm to 20 μm.

[0013] Furthermore, the fiber orientations of adjacent oriented spinning sheets are perpendicular to each other.

[0014] Furthermore, the thickness of the oriented spinning layer is 0.02 to 0.3 mm;

[0015] Preferably, the mesh spinning layer has a thickness of 0.2-1 mm;

[0016] Preferably, the thickness of the mesh spunbond layer close to the wound is greater than the thickness of the mesh spunbond layer far from the wound.

[0017] Furthermore, the fiber diameters of the mesh spinning layer and the oriented spinning sheet are independently 1 nm to 10 μm.

[0018] Furthermore, the mesh spinning layer also includes antibacterial and anti-inflammatory substances;

[0019] Preferably, the mesh spinning layer and the oriented spinning sheet are both made of degradable polyurethane materials;

[0020] Preferably, the thickness of the dressing is 0.5 to 1.5 mm;

[0021] Preferably, the tensile strength of the dressing is 28.68 to 56.67 N / cm;

[0022] Preferably, the elongation at break of the dressing is 272.67-605.31%;

[0023] Preferably, the suture strength of the dressing is 10.58 to 25.91N;

[0024] Preferably, the tear strength of the dressing is 21.29 to 57.42N;

[0025] Preferably, the bursting strength of the dressing is 258.66 to 453.56 kPa;

[0026] Preferably, the liquid absorption capacity of the dressing is ≥ 76%.

[0027] In a second aspect, the present invention provides a method for preparing the above-mentioned dressing, comprising the following steps:

[0028] A. taking a polyurethane solution with a concentration of 5% to 25% w / v as a mesh spinning solution, and preparing a mesh spinning layer by an electrospinning method;

[0029] B. taking a polyurethane solution with a concentration of 5% to 20% w / v as an oriented spinning solution, and sequentially preparing oriented spinning sheets on a mesh spinning layer by an electrospinning method to obtain an oriented spinning layer;

[0030] C. Prepare a mesh spinning layer on the other side of the oriented spinning layer prepared in step B to obtain a dressing.

[0031] Furthermore, the weight average molecular weight of the polyurethane in the web spinning solution is 5 to 12W;

[0032] Preferably, the weight average molecular weight of the polyurethane in the oriented spinning solution is 20-26W.

[0033] Further, the solvent of the polyurethane solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether;

[0034] Preferably, the solvent of the polyurethane solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran;

[0035] Preferably, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7, preferably 10:1 to 1:1;

[0036] Preferably, the method further comprises coating or impregnating the mesh spinning layer with antibacterial and anti-inflammatory substances.

[0037] Furthermore, the spinning conditions of the oriented spinning sheet include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.4ml / min, a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 200 to 700mm / min.

[0038] Preferably, the spinning conditions of the mesh spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, an injection speed of the nozzle of 0.1-0.6ml / min; a rotation speed of the receiving device of 50 to 800rpm / min, and a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 50 to 300mm / min.

[0039] In a third aspect, the present invention provides use of the above-mentioned dressing or the dressing prepared by the above-mentioned preparation method in preparing a product for promoting wound healing or preventing wound infection.

[0040] The present invention provides a dressing, which can ensure that the dressing maintains sufficient mechanical properties when the mesh spinning layer is not particularly thick by arranging at least two layers of oriented spinning sheets between the mesh spinning layers; at the same time, the fiber diameter of the oriented spinning sheet is set to 1nm-20μm, and an interlaced network is formed between the two layers of oriented spinning sheets, so that the pores of the interlaced network of the oriented spinning layer, the pores between the oriented fibers in the oriented spinning layer and the pores of the mesh spinning layer cooperate with each other to promote cell adsorption and growth; the mesh spinning layer located on the outside has a strong liquid absorption capacity, keeps the wound dry, promotes wound healing, and prevents infection. The dressing is suitable for superficial wounds on the body surface and can absorb wound exudate. At the same time, because the dressing is thin and has excellent mechanical properties, it will not cause inconvenience in the wound and will not be damaged due to limb movement. It solves the technical problems in the prior art that the superficial wound dressing is thick and affects the activity, or is thin and has poor absorption capacity and is easy to be damaged. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 A schematic diagram of the structure of a dressing provided in Example 1 of the present invention;

[0043] Figure 2 This is an electron microscope observation image of the mesh spinning layer provided in Example 1 of the present invention;

[0044] Figure 3 This is a microscopic observation image of the oriented spun sheet provided in Example 1 of the present invention.

[0045] Icon: 1-net spinning layer; 2-oriented spinning sheet. DETAILED DESCRIPTION

[0046] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0047] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.

[0048] In one aspect, the present invention provides a dressing, comprising an oriented spinning layer and a mesh spinning layer 1 respectively arranged on both sides of the oriented spinning layer;

[0049] The oriented spinning layer comprises at least two layers of oriented spinning sheets 2, and the fiber orientations of adjacent oriented spinning sheets 2 are crossed with each other;

[0050] The porosity of the oriented spinning layer is 40% to 80%; the porosity of the mesh spinning layer 1 is 50% to 85%; the fiber diameters of the mesh spinning layer 1 and the oriented spinning sheet 2 are independently 1 nm to 20 μm.

[0051] By arranging at least two layers of oriented spinning sheets 2 between the mesh spinning layer 1, it can be ensured that the dressing maintains sufficient mechanical properties when the mesh spinning layer 1 is not particularly thick; at the same time, the fiber diameter of the oriented spinning sheet 2 is set to 1nm~20μm, and an interlaced network is formed between the two layers of oriented spinning sheets 2, so that the pores of the interlaced network of the oriented spinning layer, the pores between the oriented fibers in the oriented spinning layer and the pores of the mesh spinning layer 1 cooperate with each other to promote cell adsorption and growth; the mesh spinning layer 1 located on the outside has a strong liquid absorption capacity, keeps the wound dry, promotes wound healing, and prevents infection. The dressing is suitable for superficial wounds on the body surface and can absorb wound exudate. At the same time, because the dressing is thin and has excellent mechanical properties, it will not cause inconvenience in the wound and will not be damaged due to limb movement. It solves the technical problems in the prior art that the superficial wound dressing is thick and affects the activity, or is thin and has poor absorption capacity and is easy to be damaged.

[0052] The porosity of the oriented spinning layer may be, but is not limited to, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, or any value between 40% and 80%.

[0053] The porosity of the mesh spinning layer 1 may be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, and may also be any value between 50% and 85%.

[0054] The fiber diameters of the mesh spinning layer 1 and the oriented spinning sheet 2 can be independently but not limited to 1nm, 10nm, 30nm, 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm or 20μm, and can also be any value between 1nm and 20μm.

[0055] In order to further improve the mechanical properties of the dressing, in some specific embodiments, the fibers of adjacent oriented spinning layers 2 are oriented perpendicular to each other.

[0056] In some specific embodiments, the thickness of the oriented spinning layer is 0.02-0.3 mm; in some specific embodiments, the thickness of the mesh spinning layer 1 is 0.2-1 mm. Good water absorption can be maintained.

[0057] The thickness of the oriented spinning layer may be, but is not limited to, 0.02 mm, 0.04 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.13 mm, 0.15 mm, 0.18 mm, 0.2 mm, 0.23 mm, 0.25 mm, 0.28 mm or 0.3 mm, and may be any value between 0.02 and 0.3 mm.

[0058] The thickness of the mesh spinning layer 1 may be, but is not limited to, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, and may also be any value between 0.2 and 1 mm.

[0059] In some specific embodiments, the thickness of the mesh spinning layer 1 close to the wound is greater than the thickness of the mesh spinning layer 1 far from the wound, which is more conducive to the adsorption of wound exudate without affecting the overall thickness.

[0060] In some specific embodiments, the fiber diameters of the mesh spinning layer 1 and the oriented spinning sheet 2 are independently 1 nm to 10 μm, which can facilitate cell attachment and growth, promote cell proliferation, and accelerate wound healing.

[0061] In some specific embodiments, the mesh spinning layer 1 also includes antibacterial and anti-inflammatory substances to prevent wound infection.

[0062] In some specific embodiments, the mesh spinning layer 1 and the oriented spinning sheet 2 are both made of degradable polyurethane materials.

[0063] It is further found that the dressing has excellent mechanical properties and liquid absorption. In some specific embodiments, the thickness of the dressing is 0.5-1.5 mm; in some specific embodiments, the tensile strength of the dressing is 28.68-56.67 N / cm; in some specific embodiments, the elongation at break of the dressing is 272.67-605.31%; in some specific embodiments, the suture strength of the dressing is 10.58-25.91 N; in some specific embodiments, the tear strength of the dressing is 21.29-57.42 N; in some specific embodiments, the bursting strength of the dressing is 258.66-453.56 kPa; in some specific embodiments, the liquid absorption of the dressing is ≥76%.

[0064] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned dressing, comprising the following steps:

[0065] A. taking a polyurethane solution with a concentration of 5% to 25% w / v as a mesh spinning solution, and preparing a mesh spinning layer by an electrospinning method;

[0066] B. taking a polyurethane solution with a concentration of 5% to 20% w / v as an oriented spinning solution, and sequentially preparing oriented spinning sheets 2 on a mesh spinning layer by an electrospinning method to obtain an oriented spinning layer;

[0067] C. Prepare a mesh spinning layer on the other side of the oriented spinning layer prepared in step B to obtain a dressing.

[0068] Made of degradable polyurethane material, the dressing can be used for superficial wounds on the body surface to absorb wound exudate. It has excellent mechanical properties and will not be damaged by limb movement. It does not need to be replaced during the wound repair process.

[0069] In some specific embodiments, the weight average molecular weight of the polyurethane in the web spinning solution is 5 to 12 W. In some specific embodiments, the weight average molecular weight of the polyurethane in the oriented spinning solution is 20 to 26 W.

[0070] In some specific embodiments, the solvent of the polyurethane solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether;

[0071] In some specific embodiments, the solvent of the polyurethane solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran.

[0072] In some specific embodiments, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7.

[0073] The volume ratio of N,N-dimethylformamide to tetrahydrofuran may be, but is not limited to, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 3:1 or 3:7, or any ratio between 10:1 and 3:7, preferably 10:1 to 1:1.

[0074] In some specific embodiments, the method further comprises step D of removing the solvent and drying.

[0075] In some specific embodiments, removing the solvent comprises freeze-drying to remove the solvent or soaking in water for 1 to 10 days to remove the solvent.

[0076] The soaking time in water may be, but is not limited to, 1 d, 2 d, 3 d, 4 d, 5 d, 6 d, 7 d, 8 d, 9 d or 10 d, and may also be any value between 1 and 10 d.

[0077] In some specific embodiments, the drying temperature is 30-100°C.

[0078] The drying temperature may be, but is not limited to, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, and may be any temperature between 30 and 100°C.

[0079] In some specific embodiments, the mesh spinning layer 1 is further coated or impregnated with antibacterial and anti-inflammatory substances.

[0080] Specifically, the antibacterial and anti-inflammatory substance includes at least one of penicillins, cephalosporins, macrolides or quinolones, such as penicillin, cefuroxime, erythromycin, azithromycin or levofloxacin.

[0081] In order to control the porosity of the dressing, the pores of the interwoven network of the oriented spinning layer, the pores between the oriented fibers in the oriented spinning layer and the pores of the mesh spinning layer 1 cooperate with each other to promote cell adsorption and growth. In some specific embodiments, the spinning conditions of the oriented spinning sheet include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, an injection speed of the nozzle of 0.05-0.4ml / min, a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 200 to 700mm / min. In some specific embodiments, the spinning conditions of the mesh spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, an injection speed of the nozzle of 0.1-0.6ml / min; a rotation speed of the receiving device of 50 to 800rpm / min, and a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 50 to 300mm / min.

[0082] By limiting the translation speed, the rotation speed of the receiving device and the injection speed are coordinated with each other to prepare the target porosity, and then the thickness of the dressing is controlled in combination with the spinning time.

[0083] According to another aspect of the present invention, there is also provided use of the above dressing or the dressing prepared by the above preparation method in preparing a product for promoting wound healing or preventing wound infection.

[0084] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] The dressings of the following examples and comparative examples were prepared using the method for preparing degradable polyurethane biomaterials provided by Chinese patent application number 201811568720.2.

[0086] Example 1 (1 layer of mesh spinning layer + 2 layers of cross-oriented fiber sheets + 1 layer of mesh spinning layer)

[0087] A method for preparing a dressing, the specific steps comprising:

[0088] 1. Prepare a degradable polyurethane (PU) solution 1 as a web spinning solution:

[0089] A 25% polyurethane solution was prepared by using a degradable polyurethane (weight average molecular weight Mw of 12W) as a solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a solvent.

[0090] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.

[0091] The specific preparation operations are as follows:

[0092] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.

[0093] (2) Weigh 75 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.

[0094] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.

[0095] 2. Prepare a degradable polyurethane (PU) solution 2 as an oriented spinning solution:

[0096] A 20% polyurethane solution was prepared by using a degradable polyurethane (weight average molecular weight Mw: 26W) as a solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a solvent.

[0097] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.

[0098] The specific preparation operations are as follows:

[0099] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.

[0100] (2) Weigh 60 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.

[0101] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.

[0102] 3. Electrospinning:

[0103] (1) Wipe the electrospinning machine clean and ensure that the equipment is in a clean state.

[0104] (2) Fix the release paper on the receiving device to ensure that the release paper is not loose.

[0105] (3) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.

[0106] (4) The receiver receiving speed is set to (350±100) rpm / min; the injection speed of the nozzle is set to 0.2±0.05 ml / min.

[0107] The translation speed of the nozzle was set to 100±50mm / min, and the translation distance was set to 300±50mm.

[0108] Use the prepared biodegradable polyurethane (PU) solution 1 and slowly draw the PU solution with a disposable syringe to avoid bubbles. If bubbles are generated, they must be removed before subsequent operations. Install a 22G needle (inner diameter 0.41mm) and fix the syringe in the buckle of the electrospinning machine push pump.

[0109] The nozzle diameter range can be: 0.15-4.2mm, preferably 18G (inner diameter 0.9mm), 19G (inner diameter 0.84mm), 20G (inner diameter 0.62mm), 21G (inner diameter 0.51mm), 22G (inner diameter 0.41mm), 23G (inner diameter 0.33mm) or 24G (inner diameter 0.3mm) needles. In this embodiment, a 22G needle is selected.

[0110] The negative voltage was set to (-3±1) KV, and the positive voltage was set to (9±0.5) KV. Electrospinning was started, and the spinning effect was observed until continuous and uniform yarns were ejected. The electrospinning time was set to 30 min to 3 h.

[0111] (5) After the first electrospinning, the prepared biodegradable polyurethane (PU) solution 2 was used for electrospinning, and some parameters were adjusted as follows: the receiver receiving speed was set to (1800±100) rpm / min; the injection speed of the nozzle was set to 0.2±0.05 ml / min.

[0112] The translation speed of the nozzle was set to 500±50mm / min, and the translation distance was set to 300±50mm.

[0113] The electrospinning time is 30min~1h.

[0114] The other parameters are the same as step (4).

[0115] (6) After the second electrospinning is completed, the release paper (with a spinning layer on the surface) is rotated 90° and then fixed. Repeat step (5) for the third electrospinning.

[0116] (7) After the third electrospinning, the prepared degradable polyurethane (PU) solution 1 is used for electrospinning, and step (4) is repeated for the fourth electrospinning.

[0117] 4. Post-processing

[0118] (1) Soak the electrospun membrane in a water tank for at least 7 days, changing the water twice a day and cleaning it every two days.

[0119] The ratio of the patch surface area to the water volume in each water tank should be ≥900cm 2 / L.

[0120] (2) Rinse the electrospun membrane with injection water cooled to 30°C and lay it flat on the partition rack of the oven.

[0121] The oven temperature was set at 35°C and the drying time was (5±1) h. After the electrospun membrane was dried, the appearance was inspected and then cut into the required size.

[0122] Combination Figure 1 to Figure 3 To explain, Figure 2 The scale bar in the left image is 10 μm, and the scale bar in the right image is 20 μm. Figure 3 The scale bar is 50 μm. The thickness of the oriented spinning layer of the dressing prepared in this embodiment is 0.2±0.05 mm, the fiber diameter of the oriented spinning sheet 2 is 1 nm to 20 μm, and the porosity of the oriented spinning layer is 55±10%; the thickness of the mesh spinning layer 1 is 0.6±0.05 mm, the fiber diameter of the mesh spinning layer 1 is 1 nm to 20 μm, and the porosity of the mesh spinning layer 1 is 75±10%.

[0123] Example 2

[0124] The difference from Example 1 is that when making two layers of oriented fiber sheets, one layer of oriented fiber sheets is spun first, rotated 60 degrees in the middle, and then another layer of oriented fiber sheets is spun.

[0125] Example 3

[0126] The difference from Example 1 is that the oriented spinning layer between the two mesh spinning layers has four layers of cross-oriented fiber sheets.

[0127] When making the oriented spinning layer, after the first layer of oriented fiber sheet is electrospun, the release paper is rotated 90 degrees and then fixed, and the second layer of oriented fiber sheet is electrospun; after the second layer of oriented fiber sheet is electrospun, the release paper is rotated 90 degrees and then fixed, and the third layer of oriented fiber sheet is electrospun; after the third layer of oriented fiber sheet is electrospun, the release paper is rotated 90 degrees and then fixed, and the fourth layer of oriented fiber sheet is electrospun.

[0128] Comparative Example 1:

[0129] The difference from Example 1 is that only two mesh spinning layers are prepared, and no oriented spinning sheet is prepared.

[0130] Comparative Example 2:

[0131] The difference from Example 1 is that only two layers of oriented spinning sheets are prepared, and no mesh spinning layer is prepared.

[0132] Test 1 Mechanical properties test

[0133] The mechanical properties of the dressings of Examples 1 to 3 and Comparative Examples 1 to 2 were tested respectively according to the following methods, and the specific operations included:

[0134] (1) Tensile strength: The dry samples to be tested were first cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, the tensile testing machine was turned on, the parameters were set, the tensile strength test was performed, and the data was processed. The specific results are shown in Table 1.

[0135] Tensile strength (N / cm) = tension (N) / sample width (cm).

[0136] (2) Elongation at break: First, the dry sample to be tested was cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, the tensile testing machine was turned on, the parameters were set, the elongation at break test was performed, and the data was processed. The specific results are shown in Table 1.

[0137] Elongation at break (%) = (elongation at break of sample / original length of sample) × 100%.

[0138] (3) Suture strength: First, the dry sample to be tested was cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, a suture thread of the selected specification was used to sew one end of the sample to be tested with two needles and tied to fix it. The same method was used to sew multiple specimens, and the thickness of each sample was tested with a thickness gauge. Then, a tensile testing machine was used to clamp the sample to be tested and test the suture strength of the suture to obtain the test data. The specific results are shown in Table 1.

[0139] (4) Tear strength: First, cut the dry sample to be tested into samples with appropriate width, flat edges, parallel sides and no visible defects. Use a cutter to cut along the center of the sample to prepare a trouser-shaped sample. The cutting edge of the cutter must be kept sharp without curling or notching. The cut is located in the center of the sample width. Use a thickness gauge to measure 3 points in the tear area of ​​the sample, and the arithmetic average is the thickness. Turn on the tensile testing machine, clamp the sample to be tested, and perform a tear strength test to obtain the test data. The specific results are shown in Table 1.

[0140] (5) Bursting strength: First, the dry test sample was cut into multiple square specimens with appropriate width, flat edges, parallel sides and no visible defects. The thickness of each sample was tested with a thickness gauge. Then, the tensile testing machine was turned on and the test sample was clamped to perform the bursting strength test. The test data was obtained. The specific results are shown in Table 1.

[0141] Table 1 Mechanical properties test results of different dressings

[0142]

[0143]

[0144] As shown in Table 1, the mechanical properties of the comparative example 1, which has no oriented spinning layer and only a mesh spinning layer, are poor, while the tensile strength of the dressings in Examples 1 to 3 reaches 28.68 to 56.67 N / cm, the elongation at break reaches 272.67 to 605.31%, the suture strength reaches 10.58 to 25.91 N, the tear strength reaches 21.29 to 57.42 N, and the bursting strength reaches 258.66 to 453.56 kPa. The patch of the present invention has good mechanical properties and can well meet the mechanical property requirements of the patch for tissue repair.

[0145] Test 2 Liquid Absorption Test

[0146] The liquid absorbency of the dressings of Examples 1 to 3 and Comparative Examples 1 to 2 was tested according to the following method. The test liquid consisted of a solution of sodium chloride and calcium chloride, and the liquid contained 142 mmol of sodium ions and 2.5 mmol of calcium ions. The ion content in the liquid was equivalent to human serum or wound exudate. 8.298 g of sodium chloride and 0.368 g of dihydrate chloride were dissolved in deionized water in a volumetric flask and diluted to 1 L. The specific operation included:

[0147] Accurately weigh about 1g of the dressing, recorded as m1, and place it in a culture dish; add the test solution preheated to (37±1)℃ to completely immerse the product.

[0148] Move into a drying oven and keep at (37±1)℃ for 24h.

[0149] Hold one end of the sample with tweezers, let it hang for 30 seconds, weigh it, record it as m2, and calculate the liquid absorption using the following formula.

[0150]

[0151] The specific results are shown in Table 2.

[0152] Table 2 Liquid absorption test results

[0153] sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Liquid absorption % 76.3 77.8 76.6 73.5 33.1

[0154] As shown in Table 2, the liquid absorption of the comparative example 2 which has no mesh spinning layer but only an oriented spinning layer is poor, while the liquid absorption of the dressings of Examples 1 to 3 is good.

[0155] Experiment 3 Cell proliferation ability test

[0156] Take the dressings of Examples 1 to 3 and Comparative Examples 1 to 2, and perform a cell proliferation test according to the following operation: use a puncher to make a circular specimen of the size of the bottom area of ​​a 48-well plate for each sample, sterilize it, put it into a 48-well cell culture plate, and soak it in MEM culture medium containing 10% FBS at 37°C and 60rpm for 24 hours, with the outer layer of the specimen facing the bottom of the well.

[0157] The whole process was performed in a clean bench to ensure aseptic operation. Mouse fibroblast L-929 cells grown to the logarithmic growth phase were digested with 0.25% trypsin (containing EDTA). After digestion, the cell suspension was centrifuged (1000 rpm, 5 min), the supernatant was discarded, and the cells were resuspended in MEM medium and counted to obtain 2×10 4 The soaked samples were spread in 48-well plates, and 3 samples were processed in parallel in each group.

[0158] 2×10 4 300 μL of a cell suspension of 10 cells / mL was seeded into each well of a 48-well plate and cultured in a cell culture incubator (37° C., 5% CO 2 , >90% humidity).

[0159] After 24h, 3d and 6d, the original culture medium in the 48-well plate was discarded, and 30μL of MTT solution (concentration of 5mg / mL) was added to the corresponding wells of the 48-well plate, and cultured in a 37°C, 5% carbon dioxide incubator. After 4h, the supernatant was removed, and 200μL of isopropanol was added to each well to dissolve the crystals. After the crystals were completely dissolved, the sample was taken out, and the liquid in the well was transferred to a 96-well plate, 100μL per well, and the absorbance value at a wavelength of 570nm was measured on an ELISA instrument, and compared with the OD value of the blank group, to determine whether the cells have a proliferation effect on the surface of the material, and calculate its cell proliferation rate. The results are shown in Table 3.

[0160] Table 3 Cell proliferation rate

[0161]

[0162] It can be seen from Table 3 that the dressings in Examples 1 to 3 have good cell proliferation rate effects, and the cell proliferation rate effect of the dressing composed of two layers of fiber orientation sheets and a mesh spinning layer is more significant.

[0163] Test 4 Degradation test

[0164] Take the dressings of Examples 1 to 3 and Comparative Examples 1 to 2 and conduct degradation tests according to the following procedures:

[0165] (1) Preparation of enzyme buffer:

[0166] Prepare a solution containing potassium dihydrogen phosphate and disodium hydrogen phosphate with sterile double distilled water, containing 1.653g KH2PO4 and 7.744g NaH2PO4 per liter of buffer. The pH value of the buffer solution should be 7.4±0.2. After sterilization, add 0.2g / L lipase. The salts used in the preparation are analytically pure and dried to constant weight.

[0167] (2) Degradation test:

[0168] The sample is vacuum dried at room temperature to constant weight, and the weight of the sample is accurately measured. The sample is placed in a glass container, covered with enzyme buffer and the container is sealed. The minimum volume of the buffer should be 10 mL, and the ratio of the volume of the buffer (mL) to the mass of the sample (g) should be greater than or equal to 30:1. The sample is maintained at 37 ± 1 ° C in a constant temperature water bath or oven.

[0169] (3) Determination of degradation cycle:

[0170] For sample degradation testing, samples were taken at 11 weeks, 12 weeks, 13 weeks, 25 weeks, 26 weeks, 27 weeks, 34 weeks and 35 weeks for mechanical property testing.

[0171] After wiping the liquid on the sample surface with a paper towel, the sample was loaded into the tensile testing machine fixture and tested directly. The test rate was set to 50 mm / min. The test was terminated when the sample could not be tested for mechanical properties, and the time point for stopping the test was the degradation cycle of the sample. The results are shown in Table 4.

[0172] Table 4 Degradation test results

[0173] sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Test cycle / week 26 26 35 12 26

[0174] As shown in Table 4, the degradation period of Comparative Example 1 is 12 weeks for only the mesh spinning layer and no oriented spinning layer, and 26 weeks for only the oriented spinning layer and no mesh spinning layer in Comparative Example 2. The dressings prepared in Examples 1 to 3 can be completely degraded in 26 to 35 weeks, which can provide sufficient protection for wound healing.

[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A dressing, characterized in that: It comprises an oriented spinning layer and mesh spinning layers (1) respectively arranged on both sides of the oriented spinning layer; The oriented spinning layer comprises at least two layers of oriented spinning sheets (2), and the fiber orientations of adjacent oriented spinning sheets (2) are mutually crossed; The porosity of the oriented spinning layer is 40% to 80%; The porosity of the mesh spinning layer (1) is 50%-85%; The fiber diameters of the mesh spinning layer (1) and the oriented spinning sheet (2) are independently 1 nm to 20 μm.

2. The dressing according to claim 1, characterized in that The fibers of adjacent oriented spinning sheets (2) are oriented perpendicular to each other.

3. The dressing according to claim 1, characterized in that The thickness of the oriented spinning layer is 0.02 to 0.3 mm; Preferably, the mesh spinning layer (1) has a thickness of 0.2-1 mm; Preferably, the thickness of the mesh spunbond layer (1) close to the wound is greater than the thickness of the mesh spunbond layer (1) far from the wound.

4. The dressing according to claim 1, characterized in that The fiber diameters of the mesh spinning layer (1) and the oriented spinning sheet (2) are independently 1 nm to 10 μm.

5. The dressing according to claim 1, characterized in that The mesh spinning layer (1) also includes antibacterial and anti-inflammatory substances; Preferably, the mesh spinning layer (1) and the oriented spinning sheet (2) are both made of degradable polyurethane materials; Preferably, the thickness of the dressing is 0.5 to 1.5 mm; Preferably, the tensile strength of the dressing is 28.68 to 56.67 N / cm; Preferably, the elongation at break of the dressing is 272.67-605.31%; Preferably, the suture strength of the dressing is 10.58 to 25.91N; Preferably, the tear strength of the dressing is 21.29 to 57.42N; Preferably, the bursting strength of the dressing is 258.66 to 453.56 kPa; Preferably, the liquid absorption capacity of the dressing is ≥ 76%.

6. The method for preparing the dressing according to any one of claims 1 to 5, characterized in that: The following steps are involved: A. taking a polyurethane solution with a concentration of 5% to 25% w / v as a web spinning solution, and preparing a web spinning layer (1) by an electrospinning method; B. taking a polyurethane solution with a concentration of 5% to 20% w / v as an oriented spinning solution, and sequentially preparing oriented spinning sheets (2) on a mesh spinning layer (1) by an electrospinning method to obtain an oriented spinning layer; C. Prepare a mesh spinning layer (1) on the other side of the oriented spinning layer prepared in step B to obtain a dressing.

7. The preparation method according to claim 6, characterized in that: The weight average molecular weight of the polyurethane in the web spinning solution is 5 to 12W; Preferably, the weight average molecular weight of the polyurethane in the oriented spinning solution is 20-26W.

8. The preparation method according to claim 7, characterized in that: The solvent of the polyurethane solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether; Preferably, the solvent of the polyurethane solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran; Preferably, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7, preferably 10:1 to 1:1; Preferably, the method further comprises coating or impregnating the mesh-shaped spinning layer (1) with antibacterial and anti-inflammatory substances.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The spinning conditions of the oriented spinning sheet include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.4ml / min, a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 200 to 700mm / min. Preferably, the spinning conditions of the mesh spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, an injection speed of the nozzle of 0.1-0.6ml / min; a rotation speed of the receiving device of 50 to 800rpm / min, and a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 50 to 300mm / min.

10. Use of the dressing according to any one of claims 1 to 5 or the dressing prepared by the preparation method according to any one of claims 6 to 9 in preparing a product for promoting wound healing or preventing wound infection.

Citation Information

Patent Citations

  • Degradable polyurethane biological material as well as preparation method and application thereof

    CN109851744A